PENINGKATAN KEMAMPUAN FOTOGRAFI DI JURUSAN KURIKULUM DAN TEKNOLOGI PENDIDIKAN FAKULTAS PENDIDIKAN - M. Adning (Perspektif Ilmu Pendidikan, 2006)
This action research aims at improving the competence of the students of Educational Technology Program at Faculty of Education, State University of Jakarta, in photography. After improving the instructional model in three cycles, the research found an appropriate model to improve the students’ competence covering cognitive aspect, affective aspect andpsychomotor aspect.